CONFIDENCE INTERVALS FOR THE CONTENT VALIDITY: A VISUAL BASIC COM-PUTER PROGRAM FOR THE AIKEN’S V. - Merino Soto, César; Livia Segovia, José (Anales de Psicología / Annals of Psychology, 2009)
The present document reporting a Visual Basic computer program for compute the Aiken’s V coefficient, this used for quantification of the content validity, and their confidence interval in specified levels of previously Type I error rate. The construction of confidence intervals is performed using the score method, and it was published in Penfield and Giacobbi (2004). The growing use of this method and of the confidence interval approach is fitted to the request of improving the results in infer-ential statistic procedures for the psychological research. It is discussed their use in applied context.